PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS ANIMASI MENGGUNAKAN APLIKASI CAPCUT MATERI SIKLUS AIR UNTUK SISWA KELAS V SDN TIRON 4 KEDIRI 2023-2024 - Widayanti, Tia Mei; Endang Sri Mujiwati; Sutrisno Sahari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was motivated by the results of observations carried out at SDN Tiron 4 Kediri, it was discovered that during the learning of water cycle material in class V of SDN TIRON 4 it was found that during the learning process the teacher did not use learning media. Teachers only use teaching materials in the form of student books which contain material summaries and unattractive illustrations of the water cycle. Students find it difficult if they only read the material and observe illustrations in the form of pictures of the water cycle in student books. This results in students being less able to explain the stages of the water cycle. The aim of this research and development is to determine the validity, practicality and effectiveness of animation-based learning video media using the CapCut application for water cycle material for class V students at SDN Tiron 4 Kediri. This research uses the Research and Development (R&D) research method with the ADDIE development model. The ADDIE development model has five stages, namely analysis, design, development, implementation, evaluation. The data collection instruments used were questionnaires and tests. Data analysis techniques were in the categories of validity, practicality and effectiveness.The results of this development research are: (1) The results of media validation obtained a score of 88% (very valid), material validation obtained 92% (very valid), validation of evaluation questions obtained 88% (very valid), and validation of learning tools obtained 92% ( very valid), (2) Practicality based on teacher response questionnaires obtained a score of 92% on limited trials and 90% on extensive trials as well as student response questionnaires with a score of 97.6% on limited trials and 98% on extensive trials, ( 3) Effectiveness based on evaluation results in limited trials got an average percentage of 92.6% and in extensive trials got an average percentage of 96.5%.